Integrating local wisdom into immune system worksheets: a systematic review of effects on science literacy and conceptual mastery - Remli Nelmian Simarmata; Ellianawati Ellianawati; Sudarmin Sudarmin; Novi Ratna Dewi (Lentera Negeri, 2026)
Science literacy and mastery of the concept of the immune system are essential competencies in learning biology, but they are often constrained by the abstract and complex nature of the material. It is necessary to innovate teaching materials in the form of contextual Student Worksheets (LKPD) through the integration of local wisdom to bridge this gap. This study aims to analyze the results of previous research on the development of LKPD of the immune system based on local wisdom on science literacy and concept mastery. Using the Systematic Literature Review (SLR) method with article searches in the range of 2021–2026 and the PRISMA diagram guide, 12 final articles that met the inclusion criteria were selected. The results of the study show a tendency that the integration of local wisdom into LKPD has been proven to be able to improve science literacy, concept mastery, product validity, practicality, and learning effectiveness. However, empirical studies that specifically integrate local wisdom into immune system materials have not been found, so it has the potential to become a crucial research gap. In conclusion, the development of LKPD of the immune system based on local wisdom, especially through an ethnopharmacological approach, has great potential to become a contextual, meaningful, and relevant biology learning innovation to help students concretize abstract concepts of the body's defense mechanism in accordance with cultural reality.